2009
DOI: 10.3164/jcbn.08-256
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Fermented Green Tea Extract in a Rat Model of Non-alcoholic Steatohepatitis

Abstract: Summary Oxidative stress is frequently considered as a central mechanism of hepatocellular injury in non-alcoholic steatohepatitis (NASH). The aim of this study was to investigate the effects of fermented green tea extracts (FGTE) on NASH. Rats were fed a choline-deficient high-fat diet for 4 weeks to nutritionally generate fatty livers. NASH was induced chemically by oxidative stress using repeated intraperitoneal injections of nitrite. Rats with NASH developed steatohepatitis and liver fibrosis after 6-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 23 publications
4
44
0
1
Order By: Relevance
“…18,19 Although the pathogenesis of NASH has not yet been fully elucidated, the 'two-hit' theory is widely accepted. 20 The first hit is the accumulation of fatty acids in the liver to cause steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Although the pathogenesis of NASH has not yet been fully elucidated, the 'two-hit' theory is widely accepted. 20 The first hit is the accumulation of fatty acids in the liver to cause steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…Alanine aminotransferase ALT and aspartate aminotransferase AST activities in plasma were measured using commercial enzyme assay kits Wako 3,4 . Plasma alkaline phosphatase ALP levels and choline esterase ChE were determined using standard assays 3, 4 .…”
Section: Biochemical Determinations Of Analyses Liver Damagementioning
confidence: 99%
“…Yet, there has been reported that high-fat diet may prevent the development of histologic evidence of NASH, of which fibrosis is a major components (18) . Similarly, Nakamoto and colleagues (26) , in a four week experimental study, failed to induce fibrosis associated with high-fat diet alone in rats.…”
Section: Discussionmentioning
confidence: 89%
“…It is thus expected to act on the first phase of the metabolic process characterized by increased intake of fatty acids to the liver. Since oxidative stress plays a central role in the development of steatohepatitis, Camellia sinensis was selected as a comparative natural product due to antioxidant effects of its catechins (26) . The positive control selected was a synthetic product, bezafibrate, wich is an agonist of peroxisome proliferator-activated receptors (PPAR) with lipid-lowering effects resulting from increased beta-oxidation of fat in the liver while reducing oxidative stress and directly preventing inflammation (27) .…”
Section: Ginseng Green Tea or Fibrate: Valid Options For Nonalcoholimentioning
confidence: 99%